Design of 1V rail-to-rail fully differential operational amplifier - Meiliana. (2008)
The applications of battery powered analog and mixed-signal electronic devices call for the design of analog circuits that operate at low voltage levels. At low supply voltages, especially in the range of 1V, the operation of analog circuits with appreciable signal swing is difficult, for those of conventional CMOS process.